Assessment of temperature dynamics and microbial community responses in aerobic membrane bioreactors from mesophilic to hyper-thermophilic conditions - Lê, Quang Huy (Springer Berlin Heidelberg, 2024)
This study investigates the impact of temperature variations on the performance of an aerobic membrane bioreactor (MBR) as it transitions from mesophilic (30 °C) to hyper-thermophilic (65 °C) conditions. The microbial community structure was analyzed using 16S rRNA gene sequencing to assess how temperature influences microbial diversity and composition. In mesophilic conditions, the system exhibited high alpha diversity with a Shannon index of 5.92 and 224 observed species. As the temperature increased to 45 °C and 65 °C, diversity decreased significantly, with Shannon indices of 2.54 and 2.82, and 96 and 77 observed species, respectively. Additionally, nutrient removal efficiency, particularly for ammonia and phosphorus, declined at higher temperatures. COD removal efficiency reached 96.5% at 30 °C but decreased to 57% at 45 °C before recovering to 94% at 65 °C. Notably, biomass yield at hyper-thermophilic conditions was 37% lower than at mesophilic conditions, with a yield of 0.06 gVSS/gCODremoved. These findings highlight the potential advantages of operating under hyper-thermophilic conditions, including reduced sludge production, lower nutrient requirements, and increased organic loading capacity. The results provide valuable insights into optimizing high-temperature wastewater treatment processes for more efficient and sustainable industrial applications.